Jejunal Hemolymphangioma in a Patient Presenting with Gastrointestinal Bleeding - Shao, Xiao-Dong; Wang, Le (The International Journal of Gastroenterology and Hepatology Diseases, 2022)
Background: Hemolymphangioma is rarely found in the small intestine. There have only been eight reports of hemolymphangiomas arising in the small intestine to date. The first patient was reported by Fang et al. in 2012. A small intestinal hemolymphangioma may lead to anemia and gastrointestinal bleeding. Case Presentation: We report a case of jejunal hemolymphangioma in a 49-year-old man. The patient presented with melena and anemia. He underwent double balloon enteroscopy (DBE) the antegrade approach, which demonstrated a 3.0 cm segment of jejunum with nearly 75% of the circumferential lesion with blood remnant. The raised soft lesion was in the middle of the jejunum with white patches on the surface of the mucosa. Endoscopic biopsy was not performed to avoid secondary bleeding. The patient underwent laparotomy, and partial small intestine resection was performed. A 5.0cm segment of jejunum was resected with primary anastomosis. The patient had an uneventful postoperative recovery. Macroscopic pathological examination showed a cavernous, soft and compressible tumor. Microscopic examination showed a tumor which was composed of blood and lymphatic vessels mainly located in the submucosa. The definitive histological diagnosis was jejunal hemolymphangioma. During a follow-up of 2 years, there was no further gastrointestinal bleeding. Conclusion: Small intestinal hemolymphangioma is a rare benign tumor of which clinical manifestations are nonspecific and accurate preoperative diagnosis is challenging. Endoscopic biopsy is not recommended for hemolymphangioma of the gastrointestinal tract due to the risk of severe bleeding. Complete surgical resection of the hemolymphangioma is considered the most effective treatment for small intestinal hemolymphangioma.
Keywords: small intestine